Comprehensive review of emerging trends in thermal energy storage mechanisms, materials and applications - Kwasi-Effaha, Collins Chike; Okpako, Ogheneochuko (Frontiers in Energy Research, 2025)
Thermal energy storage (TES) technologies are emerging as key enablers of sustainable energy systems by providing flexibility and efficiency in managing thermal resources across diverse applications. This review comprehensively examines the latest advancements in TES mechanisms, materials, and structural designs, including sensible heat, latent heat, and thermochemical storage systems. Recent innovations in nano-enhanced phase change materials (PCMs), hybrid TES configurations, and intelligent system integration are highlighted. The role of advanced computational methods, such as digital twins and AI-based optimization, in enhancing TES performance is also explored. Applications in renewable energy systems, industrial processes, district heating networks, and green hydrogen production are discussed, along with associated challenges and future research directions. This review aims to synthesize current knowledge while identifying pathways for accelerating the development and practical deployment of next-generation TES technologies.